Effect of Huolong moxibustion in the treatment of Children with phlegm-heat obstructing lung type of pneumonia (火龙罐治疗痰热闭肺型小儿肺炎喘嗽的效果观察) - PAN Xiaocui (潘小翠); CHEN Suling (陈素玲); CAI Jiaqian (蔡佳倩) (中西医结合护理)
Objective To investigate the effect of Huolong moxibustion in the treatment of children with phlegm-heat obstructing lung type of pneumonia. Methods Totally100 pediatric patients with phlegm-heat obstructing lung type of pneumonia were randomly divided into the control group and the observation group, with 50 cases in each group. The control group received routine basic treatment and nursing, while the observation group received Huolong moxibustion on the basis of routine treatment. The Traditional Chinese Medicine(TCM) symptom integral and length of hospital stay were compared between two groups. Results The TCM symptom integral scores were decreased in both groups after intervention, and TCM symptom integral scores in the observation group were lower than those in the control group(P＜0. 01). The length of hospital stay in the observation group was shorter than that in the control group(P＜0. 01). Conclusion Huolong moxibustion is potentially effective to relieve the clinical symptoms of phlegm-heat obstructing lung type of pneumonia in children and reduce the length of hospital stay. (目的 探讨火龙罐治疗小儿痰热闭肺型肺炎喘嗽的效果。方法 选取2023年1月—5月收治的痰热闭肺型肺炎喘嗽患儿100例, 随机分为对照组及观察组, 各50例。对照组给予常规基础治疗和护理, 观察组在对照组基础上增加火龙罐治疗。对比两组患儿中医症候积分及住院天数。结果 干预后, 两组中医症候积分较干预前下降, 且观察组中医症候积分改善优于对照组, 差异有统计学意义(P＜0. 01)。观察组平均住院天数较对照组缩短, 差异有统计学意义(P＜0. 01)。结论 火龙罐能有效改善痰热闭肺型肺炎喘嗽患儿临床症状, 缩短患儿住院天数。)